SKELETAL MATURATION EVALUATION USING MANDIBULAR SECOND MOLAR CALCIFICATION STAGES - Nizam, Fakhira; Mengal, Nasrullah; Tareen, Mirza; Hayat, Sumbal (Pakistan Armed Forces Medical Journal, 2021)
Objective: To examine the relationship between skeletal maturity and mandibular second molar calcification stages and assessing mandibular second molar as a diagnostic tool for skeletal maturity evaluation.Study Design: Cross sectional study.Place and Duration of Study: Orthodontic department, Sandeman Provincial Hospital, Quetta, from Jan to Jun 2019.Methodology: The sample size of the study 240 comprised of equal number of males and females. Inclusion criteria was defined to include the patients (male and female) with the age from 9-16 years; on the same time, patients without facial asymmetry and without prior history of facial or neck trauma/injury or surgery were considered for the present study. Exclusion criteria was defined to exclude those patients from the study hoe had the history of bone disease and major illness in past; known cases of muscular dystrophy; any congenital malformation of cervical vertebrae and tooth caries; Low quality x-ray with poor contrast.Results: The study revealed association between Demirjian Index and Cervical Vertebrae Maturation Index stages (0.875) with the statistical significance. Demirjian Index Stage H indicated the greater percentage distribution at stage 4 and 6 of Cervical Vertebrae Maturation for males. Similarly, in females, demirjian index stages G and H showed the greater percentage at stage 4 and 6 of cervical vertebrae maturation index respectively.Conclusion: Analysis indicated that cervical vertebrae maturation index and Demirjian Index (DI) occurred earlier in femalesthan males.